2019
DOI: 10.3390/mi10040258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioner Type and Downforce, and Pad Surface Micro-Texture on SiO2 Chemical Mechanical Planarization Performance

Abstract: Based on a previous work where we investigated the effect of conditioner type and downforce on the evolution of pad surface micro-texture during break-in, we have chosen certain break-in conditions to carry out subsequent blanket SiO2 wafer polishing studies. Two different conditioner discs were used in conjunction with up to two different conditioning downforces. For each disc-downforce combination, mini-marathons were run using SiO2 wafers. Prior to polishing, each pad was broken-in for 30 min with one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…For better visualization, high and low areas of all images have been accentuated through a transformation that involves taking the inverse hyperbolic sine of the height data. 16,17,[37][38][39][40][41][42] The scale bar is also kept the same for all images to allow for visual comparisons. Red indicates the highest parts of the pad surface and is, therefore, representative of asperities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For better visualization, high and low areas of all images have been accentuated through a transformation that involves taking the inverse hyperbolic sine of the height data. 16,17,[37][38][39][40][41][42] The scale bar is also kept the same for all images to allow for visual comparisons. Red indicates the highest parts of the pad surface and is, therefore, representative of asperities.…”
Section: Resultsmentioning
confidence: 99%
“…Red indicates the highest parts of the pad surface and is, therefore, representative of asperities. 16,17,[37][38][39][40][41][42] Color changes from red to yellow, and then to green, indicate decreasing heights, with a certain shade of green representing the mean surface height, indicative of interpore land areas. 16,17,[37][38][39][40][41][42] Color shifts to light blue, and then to dark blue, represent gradually decreasing heights all the way to the bottom of the pores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kwon et al [24] found that the higher the density of grains on the dressing tool, the smaller the surface roughness of the polishing pad after dressing, and the sharper the diamond, and the greater the surface roughness of the polishing pad. McAllister [25] and found that a larger wafer-to-pad contact area during polishing reduces the pressure and defects in the CMP process.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the analysis procedure is very time-consuming, which may become a major obstacle in practice. Based on the literature study, it is found that much research has been performed on the study of the establishment of deterministic kinematic models for flat polishing (such as CMP) [ 14 , 15 , 16 , 18 , 19 , 20 ], but few studies have been found on spherical polishing [ 17 ], especially about the high-speed polishing process. This leads to the fact that the high-speed polishing technology is still limited to small-size or easily polished lenses.…”
Section: Introductionmentioning
confidence: 99%